Statio amoena : sostare e vivere lungo le strade Romane - Basso, Patrizia,; Zanini, Enrico, (Archaeopress archaeology., 2016)
New archaeological research and new studies on a rich and diverse body of extra-archaeological sources have recently reported the attention of the international scientific community on the subject of parking places, within the more general theme of the smaller settlements in the Roman world and their evolution in late antiquity and early medieval times. This volume brings together contributions from scholars from three different generations, starting from different sources and methodological approaches, converging towards the construction of an area of common reflection on a theme still relatively underdeveloped. The goal is to lay the foundation for a deepening of the interdisciplinary debate and to develop new research projects.